PENGARUH PERENCANAAN SUMBER DAYA MANUSIA TERHADAP EFEKTIVITAS ORGANISASI DI KANTOR CAMAT AMANDRAYA - Suati Laia (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study was to determine the effect of human resource planning on organizational effectiveness at the Amandraya Sub-district Office, South Nias Regency. The type of research is a quantitative type that is causal (cause and effect), journals and books, with the population and sample in this study are all employees of the Amandraya Sub-district Office of South Nias Regency as many as 30 employees. The data analysis method is simple regression analysis. Based on the results of hypothesis testing research with a calculated value of 4,173> ttable 1,701, it means that there is an influence of human resource planning on organizational effectiveness at the Amandraya Sub-district Office, South Nias Regency. This research can be concluded that there is an influence of human resource planning on organizational effectiveness in the Subdistrict Office. This research can be concluded that there is an influence of human resource planning on organizational effectiveness in the Subdistrict Office